Project risk diagnostic’s instruments: diagnostic classificator (Путеводитель предпринимателя, 2020)
The most popular to date project risk diagnostic’s methods include a lot of global problems. The article «Project risk diagnostic’s instruments: diagnostic classificator» covers some of theme’s solutions.